Analgesic and antibutyrylcholinestrasic activities of the venom prepared from the Mediterranean jellyfish Pelagia noctiluca (Forsskal, 1775) - Ayed Yosra; Dellai Afef; Mansour Hedi; Bacha Hassen; Abid Salwa (BMC, 2012)
Abstract Background Toxins derived from jellyfishes have been exploited as a model for the development of new drug promising applications to treat neurodegenerative diseases. The present work is aimed to evaluate the acute toxicity of crude venom of Pelagia noctiluca and then to screen the analgesic and antibutyrylcholinestrasic (anti-BuChE) activities of the crude venom and its fractions. Methods Sephadex G75 gel was used to separate crude venom of Pelagia noctiluca, which led to some fractions. In addition, in vivo analgesic and in vitro plasma antibutyrylcholinestrasic activities were carried out with Pelagia crude venom and its fractions respectively. Results The crude venom and its fractions displayed analgesic and anti-BuChE activities at different doses without inducing acute toxicity. Fraction 2 possesses the highest analgesic and antibutyrylcholinestrasic properties. The crude venom and fraction 1 had shown to possess less significant inhibitory activity against analgesic and antibutyrylcholinestrasic models. Conclusions Based on this study, the crude venom of Pelagia noctiluca is found to be a useful tool for probing pharmacological activity. The purification and the determination of chemical structures of compounds of active fractions of the venom are under investigation.